Triathlon wetsuit removal strategy: physiological cost of running with a wetsuit - Ciulei, M.; Prado, A.; Navalta, J.; Mercer, J. A. (Journal of Human Kinetics, 2016)
Triathletes exiting the swim portion of an event have to decide on how and when to take a wetsuit off (if worn). The purpose of this study was to determine the physiological cost of running while not using a wetsuit, carrying a wetsuit, wearing a wetsuit halfway down or wearing a wetsuit fully up. Participants (n = 20, 30.9 ± 8.7 yrs, 1.71 ± 0.08 m, 71.6 ± 9.5 kg) completed four 5 min running conditions: 1) not wearing the wetsuit, 2) wearing the wetsuit fully up, 3) wearing the wetsuit halfway down, and 4) carrying the wetsuit. A rate of oxygen uptake, a heart rate, ratings of perceived exertion and stride frequency were measured and were each influenced by wetsuit condition (p < 0.05). Each variable (i.e., a rate of oxygen uptake, a heart rate, stride frequency) was lower during running while not wearing the wetsuit vs. any other condition (p < 0.05). The rate of oxygen uptake was greatest during wearing the wetsuit halfway down vs. any other condition (p < 0.05). The heart rate was not different between any of the combinations of either wearing the wetsuit fully up or halfway down or carrying the wetsuit (p > 0.05). The rating of perceived exertion was greater during wearing the wetsuit halfway down vs. carrying the wetsuit (p < 0.05). Stride frequency was lower during not wearing the wetsuit vs. wearing the wetsuit halfway down or fully up (p < 0.05). It was concluded that running with the wetsuit halfway down resulted in the greatest rate of oxygen uptake, heart rate and rating of perceived exertion.